Isokinetic leg muscle strength relationship to dynamic balance reflects gymnast-specific differences in adolescent females - Kyselovičová, Oľga; Zemková, Erika; Péliová, Katarína; Matejová, Lenka (Frontiers in Physiology, 2023)
Balance, together with other motor qualities, plays an important role in the successful execution of specific gymnastic skills. However, it is also not clear whether different demands on dynamic balance and power produced by lower limb can be observed in sport-specific differences among gymnasts of various modalities. The question also is as to what extent isokinetic leg muscle strength contributes to anterior and posterior postural stability in gymnasts. Therefore, the aim of the study was i) to compare variables of dynamic balance and isokinetic leg muscle strength in rhythmic, artistic, and aerobic gymnasts, and ii) to investigate the relationship of reach distances in anterior, posteromedial, and posterolateral directions, as well as the composite score in the Y-balance test with an isokinetic muscle strength during knee extension and flexion at different velocities in female gymnasts of various disciplines. Altogether seven aerobic, five artistic, and six rhythmic gymnasts performed the Y-balance test and isokinetic leg muscle strength test at 60°/s, 180°/s, and 300°/s. Results showed significant between-group differences in the composite score in the Y-balance test of the dominant (F = 3.536, p = .041) and non-dominant symmetry (F = 4.804, p = .015). Similarly, average power produced during knee extension and knee flexion at 60°/s, 180°/s and 300°/s differed significantly among these groups (all at p˂0.05). In addition, there was a significant relationship between the composite score of the dominant limb symmetry and isokinetic dominant limb extension strength at 60°/s (r = .54), 180°/s (r = .87), and 300°/s (r = .84) in aerobic gymnasts. The composite score of the dominant limb symmetry was also associated with isokinetic dominant limb extension strength, albeit only at 60°/s in both artistic (r = .60) and rhythmic gymnasts (r = .55). Such between-group differences may be ascribed to their different demands on maintenance of balance under dynamic conditions and leg muscle power within their sport specializations. Taking into account significant association between the dominant limb symmetry and isokinetic dominant limb extension strength, it may be concluded that both muscle strength and fast speeds contribute to dynamic balance in adolescent gymnasts.